Karya Tari Rongga Sunyi Terinspirasi dari Tradisi Luambek di Padang Pariaman - Aurelia Ivana; Ariefin Alham Jaya Putra; Oktavianus Oktavianus; Kurniadi Ilham (INDO PUBLISHING, 2026)
The dance work Rongga Sunyi was inspired by the Luambek tradition from Padang Pariaman. The choreographer’s interest arose from the unique movements of Luambek martial arts, which differ from other forms of silek (silat). In Luambek, the duel occurs without any physical contact between the performers, yet it leaves emotional and psychological wounds for the Buluih (defeated) fighter. The central issue interpreted in this work focuses on social pressure experienced by the defeated fighter, who, from the very beginning of the duel, already feels the burden and expectation to win in order not to bring shame upon their village or themselves. This work is structured into three dramatic sequences, carrying a social theme and employing a dramatic type of choreography. The choreographic method used is based on the principles written by Prof. Dr. Y. Sumandiyo Hadi in his book Aspek Dasar-Dasar Koreografi Kelompok (The Basic Aspects of Group Choreography). To strengthen the atmosphere, the choreographer incorporated live techno music as accompaniment. The performance features five female dancers, selected based on their strong character, technical ability, and expressive interpretation that aligns with the choreographer’s vision in conveying the intended social issue. The dance work, titled Rongga Sunyi, was created in the style of traditional contemporary dance and was performed at the Boestanul Arifin Adam Auditorium on January 15, 2026.